Enhancing technology literacy through the design and implementation of an IoT Module for extracurricular activity - Eka Kusumawardhani; Seno Darmawan Panjaitan; Hendro Priyatman; Hilda; Leonardus Sandy Ade Putra (University of Merdeka Malang, 2026)
Limited access to technology-based learning facilities remains a challenge for border-area schools in improving students' digital literacy. This community service program aimed to implement an Internet of Things (IoT)-based technology literacy module as an appropriate technology solution for extracurricular activities at SMA Negeri 2 Sekayam, West Kalimantan. The program addressed two main partner problems: the absence of a dedicated IoT learning resource and the limited readiness of teachers and students to conduct IoT-based learning. The activity involved 10 teacher representatives and 20 twelfth-grade students and was carried out through needs identification, module and kit development, teacher training, student IoT introduction, and evaluation. The outputs consisted of one IoT module, one supporting kit using ESP32, LED, buzzer, and relay components, and a structured extracurricular learning scenario. Quantitative evaluation using pre-test and post-test questionnaires showed that the teacher satisfaction index increased from 40.0 to 78.3 percent, while the student index increased from 37.5 to 85.0 percent. These results indicate that the program provided practical learning resources and improved the partner's readiness to continue technology-based extracurricular learning.